2014
DOI: 10.2478/s11696-013-0463-0
|View full text |Cite
|
Sign up to set email alerts
|

Montmorillonite intercalated with SiO2, SiO2-Al2O3 or SiO2-TiO2 pillars by surfactant-directed method as catalytic supports for DeNOx process

Abstract: The intercalation of natural montmorillonite with SiO2, SiO2-Al2O3 or SiO2-TiO2 pillars by the surfactant-directed method resulted in the formation of high surface area porous materials; these were tested as catalytic supports for the process of selective catalytic reduction of NO (DeNOx). The incorporation of titanium or aluminium into the structure of the silica pillars significantly increased the surface acidity of the clay samples. Iron and copper were deposited onto the surface of the pillared clays mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…The use of other alkoxides to incorporate other heteroatoms such as alumina, zirconia, or titania, alone or mixed with silica causes modifications of the physicochemical properties of the PCHs as will be seen in next sections. Nonetheless, the different rate of polymerization in the alkoxides leads to irregular distribution in the formation of the pillared gallery structure.…”
Section: Porous Clay Heterostructuresmentioning
confidence: 98%
See 1 more Smart Citation
“…The use of other alkoxides to incorporate other heteroatoms such as alumina, zirconia, or titania, alone or mixed with silica causes modifications of the physicochemical properties of the PCHs as will be seen in next sections. Nonetheless, the different rate of polymerization in the alkoxides leads to irregular distribution in the formation of the pillared gallery structure.…”
Section: Porous Clay Heterostructuresmentioning
confidence: 98%
“…Thus, the PCHs have been synthesized from vermiculite, saponite and montmorillonite with SiO 2 ,, SiO 2 −TiO 2 ,, or SiO 2 −Al 2 O 3 in the walls and they have been used as support using Fe and Cu in the selective catalytic reduction of NO x by ammonia for the elimination of nitrogen oxides emitted by stationary sources, obtaining interesting results for the Cu catalyst supported on PCH‐SiO 2 −TiO 2 . PCHs have also been used as catalytic support (Figure ) in the preferential oxidation of CO to CO 2 using CuO‐CeO 2 as active phase.…”
Section: Uses and Applications Of Pchsmentioning
confidence: 99%
“…These changes were assigned to the PCH formation [41,42]. The results suggested that the amine type used as co-surfactant influenced the textural parameters.…”
Section: Textural Propertiesmentioning
confidence: 99%
“…Cationic layered clay minerals have been intensively studied as precursors for the synthesis of catalysts for several decades [3,4,[11][12][13][14][15]. The interest from scientists and engineers is related to the great variety of clay minerals with different layered structures and containing various intralayer and interlayer chemical elements.…”
Section: Cationic Layered Clay Minerals and Their Modificationsmentioning
confidence: 99%